Disassociation between brain activation and executive function in fragile X premutation females. Issue 2 (14th October 2016) - Shelton, Annie L.; Cornish, Kim; Clough, Meaghan; Gajamange, Sanuji; Kolbe, Scott; Fielding, Joanne
Abstract: Executive dysfunction has been demonstrated among premutation (PM) carriers (55–199 CGG repeats) of the Fragile X mental retardation 1 ( FMR1 ) gene. Further, alterations to neural activation patterns have been reported during memory and comparison based functional magnetic resonance imaging (fMRI) tasks in these carriers. For the first time, the relationships between fMRI neural activation during an interleaved ocular motor prosaccade/antisaccade paradigm, and concurrent task performance (saccade measures of latency, accuracy and error rate) in PM females were examined. Although no differences were found in whole brain activation patterns, regions of interest (ROI) analyses revealed reduced activation in the right ventrolateral prefrontal cortex (VLPFC) during antisaccade trials for PM females. Further, a series of divergent and group specific relationships were found between ROI activation and saccade measures. Specifically, for control females, activation within the right VLPFC and supramarginal gyrus correlated negatively with antisaccade latencies, while for PM females, activation within these regions was found to negatively correlate with antisaccade accuracy and error rate (right VLPFC only). For control females, activation within frontal and supplementary eye fields and bilateral intraparietal sulci correlated with prosaccade latency and accuracy; however, no significant prosaccade correlations were found for PM females. This exploratory study extends previous reports of altered prefrontal neural engagement in PM carriers, and clearly demonstrates dissociation between control and PM females in the transformation of neural activation into overt measures of executive dysfunction. Hum Brain Mapp 38:1056–1067, 2017 . ©2016 Wiley Periodicals, Inc.